2022
DOI: 10.1200/op.21.00454
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Recommendation for People With Bone Metastases: Expert Consensus for Health Care Providers and Exercise Professionals

Abstract: PURPOSE: Exercise has been underutilized in people with advanced or incurable cancer despite the potential to improve physical function and reduce psychosocial morbidity, especially for people with bone metastases because of concerns over skeletal complications. The International Bone Metastases Exercise Working Group (IBMEWG) was formed to develop best practice recommendations for exercise programming for people with bone metastases on the basis of published research, clinical experience, and expert opinion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
1
58
0
4
Order By: Relevance
“…Nevertheless, in patients with advanced cancer, exercise has the potential to prevent the loss of function, control symptoms, and help maintain independence [ 26 ]. Recent reviews have evaluated that exercise interventions are safe and feasible in advanced cancer patients and in those with metastatic bone disease [ 27 , 28 , 29 , 30 ]. Furthermore, recent reviews and meta-analyses also showed that exercise interventions achieve potential benefits on quality of life, fatigue, cancer-related symptoms, and functional status outcomes [ 31 , 32 ].…”
Section: Physical Activity and Exercise Therapy In Different Therapy ...mentioning
confidence: 99%
“…Nevertheless, in patients with advanced cancer, exercise has the potential to prevent the loss of function, control symptoms, and help maintain independence [ 26 ]. Recent reviews have evaluated that exercise interventions are safe and feasible in advanced cancer patients and in those with metastatic bone disease [ 27 , 28 , 29 , 30 ]. Furthermore, recent reviews and meta-analyses also showed that exercise interventions achieve potential benefits on quality of life, fatigue, cancer-related symptoms, and functional status outcomes [ 31 , 32 ].…”
Section: Physical Activity and Exercise Therapy In Different Therapy ...mentioning
confidence: 99%
“…Patients may present with debilitating pain, pathologic fractures, and spinal cord compression as a consequence of boney metastasis [ 30 ]. Due to concerns regarding pathologic fractures, in the past, limited rehabilitation and exercise interventions were implemented for this population [ 31 ]. Newer evidence shows that exercise is safe, feasible, and beneficial for people living with bone metastasis, and although much more research is needed, early work in mixed metastatic cancer groups shows that exercise is important in preventing deconditioning and improving QOL [ 32 ].…”
Section: Exercise Prescription To Address Cancer-related Impairments:...mentioning
confidence: 99%
“…However, people with bone metastases have unique safety parameters that require consideration to ensure the health benefits of exercise medicine can be realised without the development of skeletal complications, including lesion-, cancer-, treatment-, and patient-related factors. Recognising this challenge, and a lack of resources available to healthcare providers and exercise professionals, the IBMEWG -consisting of 23 experts from across the world (i.e., Australia, Canada, Europe, UK, and USA) and clinical disciplines (i.e., exercise physiologists, physiotherapists, kinesiologists, physiatrists, medical oncologists, and radiation oncologists)was established [1].…”
Section: International Bone Metastases Exercise Working Groupmentioning
confidence: 99%
“…In 2022, the International Bone Metastases Exercise Working Group (IBMEWG) released the world's first clinical exercise recommendations as a guiding framework to support healthcare providers and exercise professionals in delivering safe exercise medicine to people with bone metastases [1]. As an international and interdisciplinary organisation dedicated to quality supportive care for all people affected by cancer, the Multinational Association for Supportive Care in Cancer (MASCC) endorses the IMBEWG produced clinical exercise recommendations, supported by MASCC Exercise Oncology and MASCC Survivorship Study Groups.…”
Section: Introductionmentioning
confidence: 99%